Energy Evolution Law of Ore-Bearing Rock during Unloading under High Static Stress and Frequent Disturbance - Chun Wang; Mei-zhi Xie; Zu-qiang Xiong; Cheng Wang; Lu-ping Cheng (Complexity)
Based on the complex engineering environment in deep rock engineering, preloaded high axial pressure, unloading of axial pressure, and impact loading were used to simulate high in situ stress, unloading of excavation, and blasting disturbance, respectively; the experimental study on frequent impact disturbances under unloading of high static load was carried out, which aimed at revealing the energy evolution law of rock. First, the equations of elastic property, plastic energy, and incident energy in the impact process are discussed by theoretical analysis. Then, it is found by further investigation that dynamic stress-strain curve and envelope curve of rock are with the same change tendency. The initial stage was short straight stage, and then linear stage appeared and was less influenced by unloading rate. The plastic energy, the ratio of reflected energy to incident energy, and the energy consumption per unit volume of rock increase during impact. The higher the preloaded axial pressure is, the greater the ratio of reflected energy to incident energy is, the smaller the ratio of transmitted energy to incident energy and the average energy dissipation per unit volume of rock are. When the unloading rate increased, the elastic energy generated by impact gradually increased, the plasticity gradually weakened, the ratio of transmitted energy to incident energy increased, and the ratio of reflection energy to incident energy decreased.